Clinical, metabolic, and psychological characteristics in patients with gastroesophageal reflux disease overlap with irritable bowel syndrome. Issue 5 (May 2015) - Hsu, Ching-Sheng; Liu, Tso-Tsai; Wen, Shu-Hui; Wang, Chia-Chi; Yi, Chih-Hsun; Chen, Jiann-Hwa; Lei, Wei-Yi; Orr, William C.; Fabio, Pace; Chen, Chien-Lin
Abstract : Objectives: Gastroesophageal reflux disease (GERD) and irritable bowel syndrome (IBS) are highly prevalent in the general population, with significant symptom overlap, whereas the interaction between both remains poorly understood. We aim to identify the clinical and psychological factors that contribute toward the overlap of GERD and IBS. Patients and methods: We carried out a case–control study among 806 GERD and 176 IBS patients from a health check-up cohort ( n =2604). All participants were evaluated using the Reflux Disease Questionnaire score, the Pittsburgh Sleep Quality Index score, the Taiwanese Depression Questionnaire score, and the State-Trait Anxiety Inventory score. Endoscopic findings were classified according to the Los Angeles classification. IBS was diagnosed on the basis of Rome III criteria, and metabolic syndrome was defined by the National Cholesterol Education Program Adult Treatment Panel III definition. Results: Among the study population, 727 individuals had GERD, 97 individuals had IBS, and 79 individuals had a diagnosis of both GERD and IBS (GERD-I). GERD-I patients had more severe GERD symptoms compared with patients with GERD or IBS alone ( P <0.0001). Moreover, GERD-I patients had more frequent healthcare-seeking behavior, decreased quality of sleep, and higher depression scores than patients with GERD ( P <0.0001) or IBS alone ( P <0.05). In addition, GERD-I patients had lower blood pressure, waist-to-hip ratio, and higher serum high-density lipoprotein levels than those with GERD alone ( P <0.05). Conclusion: GERD patients overlapping with IBS have different clinical and psychological profiles than those with GERD or IBS alone. Our study suggests that awareness of these symptom presentations will help optimize the treatment of these conditions.